Sikap peduli lingkungan masyarakat: Studi kasus masyarakat kota Bandung - Pangsuma, Nisa Sholehah; Surtikanti, Hertien Koosbandiah (Journal of Character and Environment, 2024)
The environment plays an important role in human life as a place of interaction between organisms. Every individual should have an attitude of caring about the environment in order to maintain the sustainability of life. This research aims to analyze people's environmental care attitudes and understand the supporting factors. This research uses a quantitative approach with a survey method complemented by interviews and observations. The sampling technique used was quota sampling, with sampling limited to 70 in the Bandung City area. The attitude of caring for the environment in society and students in terms of knowledge is already in a good category, but has not been implemented well. Factors that influence this include unclear legal policy regulations, the lack of a culture of social discipline, and the rise of consumer culture which contributes to more waste. Efforts are needed to increase attitudes that care about the environment with guidance, seminars, education and invitations on social media.